2004
DOI: 10.1183/09031936.04.00115304
|View full text |Cite
|
Sign up to set email alerts
|

High altitude impairs nasal transepithelial sodium transport in HAPE-prone subjects

Abstract: High-altitude pulmonary oedema (HAPE) occurs in predisposed individuals at altitudes w2,500 m. Defective alveolar fluid clearance secondary to a constitutive impairment of the respiratory transepithelial sodium transport contributes to its pathogenesis. Hypoxia impairs the transepithelial sodium transport in alveolar epithelial type II cells in vitro. If this impairment is also present in vivo, high-altitude exposure could aggravate the constitutive defect in sodium transport in HAPE-prone subjects, and thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 31 publications
2
33
1
Order By: Relevance
“…In our extremely preterm infants, we have found lower values for ASNPD and NPD than previously described in more mature preterm infants (8,24), term infants (7,25,26), and adults (27) and no increase during the first week of life or correlation to gestational age. The reason may again be the extreme immaturity, rendering the infants unable to increase their ASNPD and NPD during the first postnatal week.…”
Section: Discussioncontrasting
confidence: 46%
“…In our extremely preterm infants, we have found lower values for ASNPD and NPD than previously described in more mature preterm infants (8,24), term infants (7,25,26), and adults (27) and no increase during the first week of life or correlation to gestational age. The reason may again be the extreme immaturity, rendering the infants unable to increase their ASNPD and NPD during the first postnatal week.…”
Section: Discussioncontrasting
confidence: 46%
“…Decreased potential difference and reduced Na + transport were reported in HAPE-susceptible subjects as predisposing factor to HAPE in the in vivo study done by Sartori et al They demonstrated that an environmental factor may impair respiratory transepithelial sodium transport in humans 47) , thus suggesting that a combination of genetic and environmental mechanisms facilitates HAPE. Keeping in view the possible role of reduced alveolar fluid clearance in HAPE, prophylactic inhalation of the adrenergic agonist salmeterol, which up-regulates the clearance of alveolar fluid in animal models, was studied, and it was shown to reduce the incidence of HAPE by 50% 47,48) . Swenson et al (2002), in their study using BAL performed within a day of ascent to 4,559 m, showed that early HAPE is characterized by a protein-rich fluid containing albumin in high concentrations and an elevated red blood cell count, both in clinically ill HAPE subjects and subjects who developed HAPE in the next 24 hours 48) .…”
Section: Alveolar Fluid Clearancementioning
confidence: 99%
“…Due to the inability to assess alveolar transport activity directly, nasal transepithelial Na + transport activity is used as a surrogate marker to study the ion transport. Hypoxic conditions of high altitudes hamper nasal transepithelial Na + transport, thus impairing fluid absorption in the human lungs 47) . Decreased potential difference and reduced Na + transport were reported in HAPE-susceptible subjects as predisposing factor to HAPE in the in vivo study done by Sartori et al They demonstrated that an environmental factor may impair respiratory transepithelial sodium transport in humans 47) , thus suggesting that a combination of genetic and environmental mechanisms facilitates HAPE.…”
Section: Alveolar Fluid Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…Although not as definitively established, polymorphisms of many genes involved in vasoactive mediator generation, inflammation, and the HIF pathway have been proposed, 11,[41][42][43] along with a reduced capacity to actively reabsorb sodium and water by the alveolar epithelium. 44,45 Prevention and Treatment of HAPE A gradual ascent to high altitude such that the sleeping elevation gain is less than 500 meters per day with rest days incorporated after every 3 or 4 days has been recommended to prevent acute altitude illnesses including HAPE. 46 In those with a prior history of HAPE, prophylactic nifedipine is advised based on a randomized controlled trial in 21 HAPE-susceptible volunteers who ascended to 4559 meters.…”
mentioning
confidence: 99%